Trend of Sangha’s Administration in the Union of Myanmar in the Next Decade - Hurng, Phra Seng (Journal of International Buddhist Studies, 2023)
This research is to analyze trend of Sangha’s administration in the Union of Myanmar in the next decade and to study the Sangha administration system of the country. Furthermore, it also supposed to examine the social evidences to understand how importance monks’ role is in Buddhist society which is based on observation research methodology and documentary research method also would apply as necessarily. It also supposes to study the main reason of setting up Sangha administration, Sanghamahanayaka Committee, in Myanmar and how this administration system is affected to the Sanghaand its relation to the state from the ancient to the present time. Correspondents have often asked what has been the influence of Buddhism on the people of this country. To really evaluate the effect of Buddhism on the people of Burma, one would have to turn back to its historical emerge of Buddhism. It also would be useful to concern the pre-Buddhist culture of the country to exactly know the affection of Buddhism.